Bipolar disorder in women - Guerra, Alexandro de Borja Gonçalves (2005)
Gender differences, described in several psychiatric disorders, seem to be also present in bipolar disorder (BD). The prevalence of bipolar I disorder is equally distributed between women and men. Women seem to be at higher risk for rapid cycling and mixed mania, conditions that could make BD a disorder with a more severe course in the female sex. A marked depressive diathesis among women, greatest use of antidepressants and hormonal differences have been mentioned as hypotheses to explain these phenomenological differences. However, women and men seem to respond equally to medication. The indication of anticonvulsivants as first-line treatment in women is controversial, except for the treatment of mixed mania and, probably, rapid cycling.BD treatment during pregnancy must take into account risks related to medication effects as well as to the mother's illness. Prophylaxis in the postpartum is strongly recommended due to a great risk of recurrence in this period. Although psychotropic medication is generally contraindicated during lactation, among mood stabilizers, carbamazepine and valproate seem safer than lithium. Further studies are needed to confirm BD's course differences between women and men and to investigate possible impact on treatment effectiveness.